TRADITIONAL ARTISTS' EXPRESSIONS AND NEGOTIATION PRACTICES THROUGH VIRTUAL SPACES - Panakajaya Hidayatullah (JURNAL PAKARENA, 2022)
This ethnographic research seeks to describe the phenomenon of the artistic practices of traditional artists in looking at new technologies and media. Discourse on various performing arts events outside the mainstream, in the 'periphery' (local) areas, which are often overlooked and neglected in discussions about art. The findings in this study confirm the progressive spirit of traditional artists in Situbondo in responding to the uncertain situation due to the pandemic. Adaptation and negotiation of the technology that has been adopted, opens new perspectives, and modes of attitude towards art practices in society. Traditional artists have demonstrated good practice in terms of survival skills and a critical attitude towards modernity